INDONESIA AND SOUTH KOREA DEFENSE DIPLOMACY: CASE STUDY OF PROCUREMENT OF CHANG BOGO CLASS VESSELS IN 2010-2018 - Cheryl Manafe; Yoedhi Swastanto; Rodon Pedrason (Jurnal Pertahanan: Media Informasi ttg Kajian & Strategi Pertahanan yang Mengedepankan Identity, Nasionalism & Integrity, 2020)
Indonesia has chosen South Korea as a cooperation partner because South Korea is agreed to Indonesia's procurement policy. The research objective was to analyze the stages of procurement of Chang Bogo class submarines and the role of defense diplomacy during the process. This study uses qualitative methodology with its analysis techniques. The study concluded that the procurement of submarines succeeded in terms of the number of submarines, but the percentage of transfer technology provided had not yet reached the minimum percentage of Indonesia’s need and Indonesia must build adequate infrastructure to achieve the independence goals of the defense industry but Indonesia was still experiencing fluctuate economic condition. Therefore, the procurement of defense and security equipment tools (alpalhankam) must adjust to that condition.